1994
DOI: 10.1083/jcb.125.6.1275
|View full text |Cite
|
Sign up to set email alerts
|

Primary mouse myoblast purification, characterization, and transplantation for cell-mediated gene therapy.

Abstract: Abstract. The transplantation of cultured myoblasts into mature skeletal muscle is the basis for a new therapeutic approach to muscle and non-muscle diseases: myoblast-mediated gene therapy. The success of myoblast transplantation for correction of intrinsic muscle defects depends on the fusion of implanted cells with host myofibers. Previous studies in mice have been problematic because they have involved transplantation of established myogenic cell lines or primary muscle cultures. Both of these cell populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
736
1
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 896 publications
(753 citation statements)
references
References 52 publications
13
736
1
3
Order By: Relevance
“…Mononucleated myoblasts spontaneously fuse with large multinucleated myotubes, 'sharing' their gene products. 29 Myoblasts are reportedly more efficiently transduced than myotubes by adenovirus recombinants; 30 the same comparison has not been done using rAAV. The efficient transduction of myotubes that we observed could result from primary AAV infection of differentiated myotubes or infection of myoblasts with subsequent formation of fusion myofibers.…”
Section: Discussionmentioning
confidence: 99%
“…Mononucleated myoblasts spontaneously fuse with large multinucleated myotubes, 'sharing' their gene products. 29 Myoblasts are reportedly more efficiently transduced than myotubes by adenovirus recombinants; 30 the same comparison has not been done using rAAV. The efficient transduction of myotubes that we observed could result from primary AAV infection of differentiated myotubes or infection of myoblasts with subsequent formation of fusion myofibers.…”
Section: Discussionmentioning
confidence: 99%
“…17 In vitro transfection and transduction Primary myoblasts derived from 3-day-old S4/129 (wildtype) and W1/129 (ANT1-deficient) mouse gastrocnemius muscle were purified to 499%. 34 Myoblasts grown in GM medium (Ham's F10 (Gibco), 20% FBS (Hyclone), 5 ng/ml bFGF (Promega)/5% CO 2 /371C) on dishes coated with E-C-L matrix (Upstate Biotech) were plated in 24-well tissue culture plates and plating efficiency was controlled to avoid significant variation among groups. At 48 h after plating, cells were transduced with the viral vectors, either with AAV-ANT1 plus pTR-UF1 at a 1:1 ratio or with AAV-ANT1 alone.…”
Section: Vector Construction and Amplificationmentioning
confidence: 99%
“…Previous experiments have shown that early preplates (pp1-2) contain a majority of fibroblasts (5-15% desmin-positive) and the late preplates (pp5-6) are enriched with desmin-positive cells (>80%). [20][21][22]41 The cells used in this experiment were taken from the late preplate (pp6) and were shown to express myogenic and stem cell markers. 9 The proliferation medium used to grow the cells was Dulbecco's modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 10% horse serum (HS) and 1% penicillin/streptomycin.…”
Section: Purification Of Primary Muscle-derived Cellsmentioning
confidence: 99%
“…20 These cells were harvested from a muscle biopsy and purified by the preplate technique based on their adherence characteristics to collagen-coated flasks. [20][21][22] The purified MDC (pp6) used for these experiments took about 6 days to adhere to collagen-coated flasks and stained positive for myogenic (desmin) and well-known stem cell markers, including Sca-1 and FLK-1. 9 These results suggest that this population of highly purified MDC may contain stem cells.…”
Section: Introductionmentioning
confidence: 99%